2021
DOI: 10.3390/math9161838
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Personal and Contextual Variables of the Global Entrepreneurship Monitor through the Rasch Mathematical Model

Abstract: This article studies the variables of entrepreneurship at the regional (countries) level proposed by the Global Entrepreneurship Monitor (GEM) in its periodic global reports. This response to the suggestions and concerns of various authors is related to the need to analyze the theoretical foundation of the variables used by GEM. The validity and reliability of GEM data for the scientific study of entrepreneurship are also analyzed. Finally, the potential of GEM data to manage entrepreneurship variables at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 148 publications
6
11
0
Order By: Relevance
“…It is accepted in the literature on entrepreneurship at the regional level that entrepreneurs are the critical element in the process of creating a new venture. This is why entrepreneurship requires entrepreneurial behaviour (intention and action) [1,2,30]. In turn, it has been found that entrepreneurial behaviour depends on contextual variables and personal variables, the latter having been more studied [37,38].…”
Section: Variables Influencing Entrepreneurial Behaviour According To...mentioning
confidence: 99%
See 4 more Smart Citations
“…It is accepted in the literature on entrepreneurship at the regional level that entrepreneurs are the critical element in the process of creating a new venture. This is why entrepreneurship requires entrepreneurial behaviour (intention and action) [1,2,30]. In turn, it has been found that entrepreneurial behaviour depends on contextual variables and personal variables, the latter having been more studied [37,38].…”
Section: Variables Influencing Entrepreneurial Behaviour According To...mentioning
confidence: 99%
“…It is mainly due to the small number of variables they incorporate [69,70]. On the other hand, the authors of predictive behavioural studies need quality traditional data sources for a wide range of variables and countries [30]. In order to respond to these demands, several authors suggest enriching predictive models by incorporating new variables and new relationships, as well as variables that, together with intention, reflect effective entrepreneurial behaviour [71].…”
Section: Variables Influencing Entrepreneurial Behaviour According To...mentioning
confidence: 99%
See 3 more Smart Citations